Characterization of TR‐107, a novel chemical activator of the human mitochondrial protease ClpP. Issue 4 (5th August 2022) - Fennell, Emily M. J.; Aponte‐Collazo, Lucas J.; Wynn, Joshua D.; Drizyte‐Miller, Kristina; Leung, Elisa; Greer, Yoshimi Endo; Graves, Paul R.; Iwanowicz, Andrew A.; Ashamalla, Hani; Holmuhamedov, Ekhson; Lang, Henk; Karanewsky, Donald S.; et al.
Abstract: We recently described the identification of a new class of small‐molecule activators of the mitochondrial protease ClpP. These compounds synthesized by Madera Therapeutics showed increased potency of cancer growth inhibition over the related compound ONC201. In this study, we describe chemical optimization and characterization of the next generation of highly potent and selective small‐molecule ClpP activators (TR compounds) and demonstrate their efficacy against breast cancer models in vitro and in vivo. We selected one compound (TR‐107) with excellent potency, specificity, and drug‐like properties for further evaluation. TR‐107 showed ClpP‐dependent growth inhibition in the low nanomolar range that was equipotent to paclitaxel in triple‐negative breast cancer (TNBC) cell models. TR‐107 also reduced specific mitochondrial proteins, including OXPHOS and TCA cycle components, in a time‐, dose‐, and ClpP‐dependent manner. Seahorse XF analysis and glucose deprivation experiments confirmed the inactivation of OXPHOS and increased dependence on glycolysis following TR‐107 exposure. The pharmacokinetic properties of TR‐107 were compared with other known ClpP activators including ONC201 and ONC212. TR‐107 displayed excellent exposure and serum t 1/2 after oral administration. Using human TNBC MDA‐MB‐231 xenografts, the antitumor response to TR‐107 was investigated. Oral administration of TR‐107 resulted in a reduction in tumor volume and extension of survival in the treated compared with vehicle control mice. ClpP activation in vivo was validated by immunoblotting for TFAM and other mitochondrial proteins. In summary, we describe the identification of highly potent new ClpP agonists with improved efficacy against TNBC, through targeted inactivation of OXPHOS and disruption of mitochondrial metabolism. Abstract : Compounds tested for mitochondrial ClpP activation and binding, potent inhibition of breast cancer cell growth. TR107 selected and examined against multiple mitochondrial parameters. Efficacy of tumor regression by TR107 shown using MDA‐MB‐231 xenograft model.